Exploratory study of reactive agility and sprint performance during Ramadan intermittent fasting in male adolescent handball players from a Tunisian club - Bedoui, M. R.; Ltifi, M. A.; Bourezgui, A.; Sufaru, C.; Pavel, S. I.; Sandovici, A.; Alexe, D. I.; Aouadi, R. (Frontiers in Physiology, 2026)
Background: This exploratory study investigated performance changes across the Ramadan period in adolescent U18 male handball players, focusing on reactive agility, linear sprint performance, and pre-planned change-of-direction (Modified Agility Test: MAT) in U18 male handball players. Given the observational design, findings should be interpreted cautiously.